Is There a Cost-Effective Means of Training Microenterprises? - Brooks, Wyatt; Donovan, Kevin; Johnson, Terence R. (Published by Oxford University Press on behalf of the World Bank, 2021)
Despite billions of dollars spent by policy institutions and academics, very few programs designed to increase managerial skills among microenterprises are cost-effective. This short paper highlights a mentorship program designed to provide managerial skills to Kenyan microenterprises, and it provides a detailed cost-benefit analysis. For each dollar spent on a treated firm, average profit increases by 1.63 USD; the result stems from both a higher program impact and lower cost relative to existing training programs. Motivated by this increased cost-effectiveness, the study then compares the program to the large literature focusing on “supply-side” interventions designed to increase managerial capacity in small firms, and it highlights particular margins on which mentorship improves on classroom training and also where training should focus.